Pengaruh User Experience terhadap Customer Satisfaction pada Aplikasi Seluler Streaming Vidio - Hafizh Arkaan Ramadhan; Btari Mariska Purwaamijaya; Rangga Gelar Guntara (Jurnal Teknologi Informasi dan Multimedia, 2023)
Business development through innovation in various industries is affected by rapid changes caused by various factors. The media and entertainment industry is showing an increase in revenue from year to year and is expected to continue growing until 2026. The average time spent by internet users in Indonesia watching broadcast and streaming for 2 hours 53 minutes per day has an impact on over-the-top penetration in Indonesia. The number of over-the-top platforms in entertainment media requires each company to innovate in the development of its services to be at the forefront. Vidio has the highest number of over-the-top service users in Indonesia. However, there are some negative reviews from users are related to the Vidio mobile app. Therefore, as an over-the-top media service from Indonesia, Vidio needs a great user experience to continue to increase users and customers. This study aims to determine the characteristics of Vidio mobile application customers and analyze the effect of user experience on customer satisfaction. Research data were obtained through observation and distributing questionnaires via the internet using convenience sampling technique from 136 active customers of Vidio mobile application. Data analysis uses validity test, reliability test, descriptive data analysis, classical assumption test, and hypothesis testing. The results showed that user experience has a positive and significant effect on customer satisfaction.